2019
DOI: 10.1002/pssa.201900534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cryogenic Dry Etching on Minority Charge Carrier Lifetime in Silicon

Abstract: Micro‐ and nanostructured silicon surface application is a promising way of photovoltaic development. An enhancement of optical absorption in solar cells can be achieved, for example, using vertically aligned silicon nanostructures with high aspect ratios. Cryogenic plasma etching is a suitable method for such structures' formation; however, there is still lack of data describing an effect of cryogenic inductively coupled plasma (ICP) etching on defect formation in silicon (Si). The defects may act as recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…Lifetime may be recovered by removing the damaged layer. [25] A special cleaning procedure was developed to prepare the samples before a-Si:H/c-Si heterojunction formation. The removal of residues of polystyrene spheres was carried out by boiling the samples sequentially in CCl 4 , and then in isopropyl alcohol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifetime may be recovered by removing the damaged layer. [25] A special cleaning procedure was developed to prepare the samples before a-Si:H/c-Si heterojunction formation. The removal of residues of polystyrene spheres was carried out by boiling the samples sequentially in CCl 4 , and then in isopropyl alcohol.…”
Section: Methodsmentioning
confidence: 99%
“…First, a 1D model was applied to verify the effect of interfaces states on photoelectric properties of planar a-Si:H/c-Si heterojunction solar cells using AFORS-HET software. The I-V curves and external quantum efficiency (EQE) spectra calculated using the model described in the study by Kudryashov et al, [25] which takes into account the effect of interface states, are shown in Figure 1. The density of interface states (D it ) has a significant influence on open-circuit voltage (V OC ) and fill factor, but at the same time D it does not almost affect the EQE spectra and short-circuit current.…”
Section: Simulationmentioning
confidence: 99%
“…Стандартные образцы с известным временем жизни и размерами, рекомендованными в международном стандарте [21], могут быть оптимальными при использования их для калибровки и поверки как контактных, так и бесконтактных средств измерения этого параметра. Но при этом необходимо четко регламентировать процедуру расчета эффективного времени жизни, пересчета его в объемное, или условия измерения, при которых эти параметры совпадают [22][23][24][25]. The article is devoted to the presentation and discussion of the primary results of an experimental study of the possibility of using the modern "transient photoconductance method" and "non-contact quasi steady state photoconductivity method" for a more accurate, accelerated and non-destructive determination of the lifetime of charge carriers in silicon wafers, intended as a base material for the manufacture of high-speed p-n-microelectronic devices and highperformance solar cells.…”
Section: заключениеunclassified
“…Two more papers also deal with Si nanocrystals, one with the enhancement of the photoluminescence by a metal membrane, the other one with the general crystallization behavior . Four contributions focus on photovoltaic applications: An improved wet‐chemical processing of Si for heterojunction solar cells, a deeper understanding of contact resistivity measurements via the TLM‐method, and the fabrication of nanostructures for enhanced light absorption by cryogenic dry etching and by using self‐assembled nanosphere‐lithography masks . Raman and infrared spectroscopy of Si nanowires with high free carrier densities are studied in ref.…”
mentioning
confidence: 99%